Design Study for a Quasisynchronous CDMA Sensor Data Collection System: An LEO Satellite Uplink Access Technique Based on GPS - Yijun Chen; Sheng Ding; Zhouchen Xie; Zhuangping Qi; Xuwen Liang (International Journal of Distributed Sensor Networks)
With the development of the LEO satellite communication technology, highly dependable wireless communication and sensor data collection using LEO satellites have been getting much attention for emergency, marine research, and forest fire disaster in the remote region. The satellite system is expected to have the following features: rapid production, low cost, and fast construction of the satellite network. In this paper, a QS-CDMA uplink access technique in the LEO satellite is presented and discussed, which is focused on the local clocks using GPS 1PPS timing signals and the Doppler compensation for terminal uplink. The spreading code with length of 1023, which is used for the uplink preamble, selects the shift-m-sequence that can greatly reduce the MAI and increase the number of simultaneous access users. A novel analysis method for the accuracy of clock synchronization and a novel method for the estimation of Doppler shift and propagation delay are presented. These methods are used to guide the specific hardware implementation of the QS-CDMA LEO satellite sensor data collection system. Through simulations and experiments, it results in that this system structure can drastically reduce the complexity in implementing the acquisition in the satellite and increase the adaptability of the satellite system in different environments.